Enhancing fish drying efficiency and quality: A comparative study of intermittent microwave convective drying (IMCD) and conventional methods - Mohammad U.H. Joardder; Abdul Mojid Parvej; Md. Fahim Shahriar; Md. Fahim Faysal; Md. Mostafizur Rahman; Azharul Karim (Future Foods)
Microwave (MW) heating offers a unique drying mechanism which pushes internal moisture to the surface during the drying of water-rich foods including fish. However, the continuous application of MW energy causes excessive localized heating, resulting in the deterioration of food quality. Although intermittent microwave convective drying (IMCD) is recognized as an advanced drying technology that addresses the limitations of conventional microwave, convective, and combined microwave convective drying methods, its practical application remains limited. Notably, there is inadequate research on the use of IMCD for fish drying. This study addresses this critical gap by investigating the effects of microwave intermittency on drying kinetics, energy consumption, and key quality attributes of fish, including shrinkage, rehydration capacity and visual appearance. Convective drying (CD), microwave convective drying (CMW) drying and IMCD, was conducted to compare the drying kinetics energy consumption and quality of dried fish fillet. It was found that IMCD took only 12 min to complete the drying process, whereas CD took approximately 300 min. IMCD provided achieved better, dried fish samples achieved superior quality, drying time was reduced by 90 % and energy consumption was reduced by 20 % in comparison with convective drying. Moreover, pattern of shrinkage, changes of colour, uniformity of colour, rehydration capasity are found better in the IMCD dried fish sample. These findings clearly establish IMCD as the best drying method for fish drying particularly at industry level. MW drying takes around 10–20 times less time than convective drying to remove the same quantity of moisture. IMCD exhibits an exergy efficiency of 23.84 %, which is higher than convective drying (14.99 %) and closer to CMW drying (21.45 %). This indicates that IMCD has a more efficient utilization of energy for useful work output. The appearance and protein content properties of the IMCD dried fish fillet appeared better than those of CD and CMW dried samples. Furthermore, the least shrinkage and superior rehydration capacity were observed in IMCD dried samples. This study also identifies the need for further optimization and integration of real-time monitoring technologies to enhance energy efficiency and product quality, highlighting the broader industrial relevance and future development potential of IMCD in fish drying applications.